Natural Killer Cells and Type 1 Innate Lymphoid Cells Are New Actors in Non-alcoholic Fatty Liver Disease - Luci, Carmelo; Vieira, Elodie; Perchet, Thibaut; Gual, Philippe; Golub, Rachel (Frontiers in Immunology, 2019)
ABSTRACT Obesity and associated liver diseases (Non Alcoholic Fatty Liver Disease, NAFLD) are a major public health problem with increasing incidence in Western countries (25% of the affected population). These complications develop from a fatty liver (steatosis) to an inflammatory state (steatohepatitis) evolving towards fibrosis and hepatocellular carcinoma. Lipid accumulation in the liver contributes to hepatocyte cell death and promotes liver injury. Local immune cells are activated either by Danger Associated Molecular Patterns (DAMPS) released by dead hepatocytes or by bacterial products (PAMPS) reaching the liver due to increased intestinal permeability. The resulting low-grade inflammatory state promotes the progression of liver complications towards more severe grades. Innate lymphoid cells (ILC) are an heterogenous family of five subsets including circulating Natural Killer (NK) cells, ILC1, ILC2, ILC3 and lymphocytes tissue-inducer cells (LTi). NK cells and tissue-resident ILCs, mainly located at epithelial surfaces, are prompt to rapidly react to environmental changes to mount appropriate immune responses. Recent works have demonstrated the interplay between ILCs subsets and the environment within metabolic active organs such as liver, adipose tissue and gut during diet-induced obesity leading or not to hepatic abnormalities. Here, we provide an overview of the newly roles of NK cells and ILC1 in metabolism focusing on their contribution to the development of NAFLD. We also discuss recent studies that demonstrate the ability of these two subsets to influence tissue-specific metabolism and how their function and homeostasis are affected during metabolic disorders.